Vertrag, Treueid, und Bund: Studien zur Rezeption des altorientalischen Vertragsrechts im Deuteronomium und zur Ausbildung der Bundestheologie im Alten Testament - Koch, Christoph (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft 0934-2575, 2008)
The notion that God, Yahweh, concluded a "Covenant" or "Contract" with his people of Israel plays a prominent part in the Old Testament. Numerous correspondences between the texts of Ancient Oriental contracts and the Book of Deuteronomy suggest that political treaties served as model for the theology of the biblical covenant. Using extant source material, the present study attempts to trace the complicated path into the Old Testament taken by an instrument used for the exercise of power in the Ancient Orient